Birth Weight and Risk of Type 2 Diabetes Mellitus, Cardiovascular Disease, and Hypertension in Adults: A Meta‐Analysis of 7 646 267 Participants From 135 Studies. Issue 23 (4th December 2018) - Knop, Marianne Ravn; Geng, Ting‐Ting; Gorny, Alexander Wilhelm; Ding, Renyu; Li, Changwei; Ley, Sylvia H.; Huang, Tao
Abstract : Background: Low birth weight has been associated with increased risk of type 2 diabetes mellitus, cardiovascular disease, and hypertension, but the risk at high birth weight levels remains uncertain. This systematic review and meta‐analysis aimed to clarify the shape of associations between birth weight and aforementioned diseases in adults and assessed sex‐specific risks. Methods and Results: We systematically searched PubMed, EMBASE, and Web of Science for studies published between 1980 and October 2016. Studies of birth weight and type 2 diabetes mellitus (T2DM), cardiovascular disease (CVD), and hypertension were included. Random‐effects models were used to derive the summary relative risks and corresponding 95% confidence intervals.We identified 49 studies with 4 053 367 participants assessing the association between birth weight and T2DM, 33 studies with 5 949 477 participants for CVD, and 53 studies with 4 335 149 participants for hypertension and high blood pressure. Sex‐specific binary analyses showed that only females had an increased risk of T2DM and CVD at the upper tail of the birth weight distribution. While categorical analyses of 6 birth weight groups and dose‐response analyses showed J‐shaped associations of birth weight with T2DM and CVD, the association was inverse with hypertension. The lowest risks for T2DM, CVD, and hypertension were observed at 3.5 to 4.0, 4.0 to 4.5, and 4.0 to 4.5 kg, respectively. Conclusions: These findings indicate that birth weight is associated with risk of T2DM and CVD in a J‐shaped manner and that this is more pronounced among females.